Development of Interactive E-Module to Foster EFL Students’ Critical Thinking in Essay Writing - Happy Kusuma Wardani; Ellys Kumala Pramartaningthyas; Taufiqur Rohman; Alimin Alimin (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop an interactive E-Module to enhance creative thinking among EFL students in academic writing, specifically essay writing. This study used research and development (R&D) with the ADDIE model, which encompasses five stages: Analysis, Design, Development, Implementation, and Evaluation. The subject of this study involved 23 students of the English Language Education Study Program from a state university in Gresik, Indonesia. The research instruments included questionnaires and interviews in the need analysis stage, validation forms in the development stage to obtain review and recommendations from the expert validators, and evaluation questionnaires to discover students’ responses towards the implementation of the E-Module. Data were analyzed using mixed methods of descriptive qualitative and quantitative. The results showed that experts validated E-Module’s high quality, with minor revisions. In addition, students’ responses indicated strong effectiveness, with 83% reporting improved understanding and motivation. Furthermore, experts and students confirmed that the E-Module demonstrated practicality through ease of use and structured progression. Overall, experts and students perceive the interactive E-Modul developed in this study as a valuable tool for fostering critical thinking and independent learning.